2007
DOI: 10.1158/0008-5472.can-06-4152
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Loss of Heterozygosity and Copy Number Analysis in Melanoma Using High-Density Single-Nucleotide Polymorphism Arrays

Abstract: Although a number of genes related to melanoma development have been identified through candidate gene screening approaches, few studies have attempted to conduct such analyses on a genome-wide scale. Here we use Illumina 317K whole-genome single-nucleotide polymorphism arrays to define a comprehensive allelotype of melanoma based on loss of heterozygosity (LOH) and copy number changes in a panel of 76 melanoma cell lines. In keeping with previous reports, we found frequent LOH on chromosome arms 9p (72%), 10p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
164
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(190 citation statements)
references
References 38 publications
25
164
1
Order By: Relevance
“…11 In human disease study, PTPRD has been reported as a tumor suppressor gene. As previously reported, PTPRD is potentially involved in carcinogenesis of lung cancer, 12 -14 cutaneous squamous carcinomas, 15 hepatomas, 16 melanomas 17 and neuroblastomas. 18 Though some receptor-like PTPs, such as CD45, RPTP-e and CD148, play an important role in lymphocyte activation, 19 PTPRD does not demonstrate potential function to immune response as yet.…”
Section: Discussionsupporting
confidence: 56%
“…11 In human disease study, PTPRD has been reported as a tumor suppressor gene. As previously reported, PTPRD is potentially involved in carcinogenesis of lung cancer, 12 -14 cutaneous squamous carcinomas, 15 hepatomas, 16 melanomas 17 and neuroblastomas. 18 Though some receptor-like PTPs, such as CD45, RPTP-e and CD148, play an important role in lymphocyte activation, 19 PTPRD does not demonstrate potential function to immune response as yet.…”
Section: Discussionsupporting
confidence: 56%
“…All cell lines were grown at 7% CO 2 , 371C in medium containing 100 U ml À1 penicillin and 100 mg ml À1 streptomycin. SK29-MEL (Wolfel et al, 1995), MZ7-MEL cells (Lennerz et al, 2005), D03-, D05-, and D14-MEL (Pavey et al, 2004;Stark and Hayward, 2007), and A365, Malme 3M, G361, and RPMI7951 (Haapajarvi et al, 1999) cells were described previously. N-methyl-N 0 -nitro-N-nitrosoguanidine (MNNG; Sigma, Munich, Germany) stocks were prepared by dissolving the drug in dimethyl sulphoxide (DMSO) and then diluting with sterile dH 2 O to a 10 mM concentration.…”
Section: Cell Culture and Drug Treatmentmentioning
confidence: 99%
“…Homozygous deletion of PTPRD has been reported at a frequency of 8-20% in lung cancer, melanoma, neuroblastoma, glioblastoma multiforme, laryngeal SCC and lymphoma. [13][14][15][16][17][18][19] Mutations of the coding exons of PTPRD and methylation at the promoter region have also been reported in lung cancer, melanoma, glioblastoma, breast and colorectal cancers, indicating that multiple mechanisms of disruption affect this gene in cancer. 17,[20][21][22] The overexpression of PTPRD in vitro causes transient growth arrest and an increase in apoptotic cells, with the converse demonstrated for the knockdown of PTPRD.…”
mentioning
confidence: 99%